80/20 running : run stronger and race faster by training slower - Fitzgerald, Matt (NAL, New American Library, 2014)
"TRAIN EASIER TO RUN FASTER This revolutionary training method has been embraced by elite runners-with extraordinary results-and now you can do it, too. Respected running and fitness expert Matt Fitzgerald explains how the 80/20 running program-in which you do 80 percent of runs at a lower intensity and just 20 percent at a higher intensity-is the best change runners of all abilities can make to improve their performance. With a thorough examination of the science and research behind this training method, 80/20 Running is a hands-on guide for runners of all levels with training programs for 5K, 10K, half-marathon, and marathon distances. In 80/20 Running, you'll discover how to transform your workouts to avoid burnout. Runs will become more pleasant and less draining. You'll carry less fatigue from one run to the next. Your performance will improve in the few high-intensity runs. Your fitness levels will reach new heights. 80/20 Running promotes a message that all runners-as well as cyclists, triathletes, and even weight-loss seekers-can embrace: Get better results by making the majority of your workouts easier."--